Laboratory Study Of Calcium Sulfate Solubility Calculation By Using Skillman, Mcdonald, And Stiff Method - Darwita Darwita (Scientific Contributions Oil and Gas, 2010)
Calcium sulfate scale is one of serious problems and must be solved accurately in petroleum industry. It can plug pore media consequently decreases production rate. Therefore, it is very important to know injection water quality of S1, S2, S3 water samples by means of calculating CaSO4 solubility. Each injection water sample has different CaSO4Â  solubility. The CaSO4 solubility of S3 produced water is usually higher than S2 and S1 solubility. Because it contains the highest calcium and sulfate ion concentrations compared with S2 and S1. No CaSO4 scale is found in all analyzed water sample.